(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
This study was conducted to differentiate among Ocimum species and subspecies grown in Sudan on basis of growth analysis. Seven different plant materials were used in this experiment. The layout of the experiment was Randomized Complete Block Design with three replicates; treatments were the Ocimum species and subspecies. Growth parameters were evaluated in terms of plant height, number of branches per plant, fresh biomass per plant (g) & productivity (ton / hectare), moisture content of leaves, Number of days to start of flowering and Number of weeks from sowing to maturity. Data collected were statistically analyzed The highest plant height (115.1cm) was obtained from O. basilicum L. (Baladi), while the lowest plant height (64.7 cm) was obtained from O. americanum L. (Wild). The highest number of branches per plant (859) was obtained from O. americanum L. (Wild), while the lowest number of branches per plant (386) was obtained from O. basilicum L. (Green). There were no significant differences among spp. for the fresh biomass per plant and productivity of fresh biomass (ton/ hectare); the highest values 1349 g / plant and 48.1 ton / hectare were recorded from O. basilicum L. (Baladi) and the lowest values 494 g/plant and 17.6 ton / hectare were recorded from O. americanum L. (Lime). The highest moisture content of leaves (86%) was obtained from O. basilicum L. (Green), while the lowest moisture content (78%) was obtained from O. tenuiflorum L. (Clove). The shortest number of days to start of flowering (39 days) and the shortest number of weeks to maturity (21.5 weeks) were obtained from O. americanum L. (Wild), while the latest start of flowering (113 days) and the latest maturity (53.7 weeks) was obtained from O. basilicum var. thyrsiflorum L. (White).